Dispute Resolution Through Mediation in the Court (Court Annexed Mediation) After the Enactment of Supreme Court Regulation No. 1 of 2016 - Siswara, Majedi Hendi; Asikin, Zainal; Djumardin, (International Journal of Scientific Research and Management (IJSRM), 2019)
This research aims to examine how the Procedure for Dispute Resolution Through Mediation in the Court and what are the consequences of the enactment of Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures. This study uses a normative method with a statutory approach and a case approach. The findings from the results of this study that with the enactment of Supreme Court Regulation No.1 of 2016, it turns out that it can accelerate the process of settling cases to 30 days and alleviate the costs of cases. Another finding is that there has been a significant increase in settlement of mediation cases compared to the enactment of Supreme Court Regulation No.1 of 2016.